2008
DOI: 10.5194/aab-51-438-2008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation for length of productive life in Slovak Pinzgau cattle

Abstract: The proportional hazards method was used to estimate breeding values for functional length of productive life within the endangered Slovak Pinzgau population. The analyzed data set contained 21,985 cows, daughters of 254 sires. The risk of culling was higher for cows with lower milk production relative to herd average, higher age at first calving and in herds decreasing in size. In the first lactation the culling risk was highest at the beginning, and decreased during lactation. From second lactation onwards a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 19 publications
10
35
0
2
Order By: Relevance
“…Selected traits of the udder belong among functional traits affecting the length of productive life (MéSZáROS et al 2008). The values of the external proportions of the teat were higher in Czech Fleckvieh cows (C) in comparison with Holstein (H).…”
Section: Resultsmentioning
confidence: 99%
“…Selected traits of the udder belong among functional traits affecting the length of productive life (MéSZáROS et al 2008). The values of the external proportions of the teat were higher in Czech Fleckvieh cows (C) in comparison with Holstein (H).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, our simulation was also based on a TMI scenario, so that practical selection can follow the new setup in the near future. For setting up the TMI, EBV for a 305-day milk production (BS SR, 2009), functional length of productive life (Mészáros et al, 2008) and live weight at 210 days of age (Kasarda et al, 2009) were used. As stated by Lin and Allaire (1977), the selection index is inherited.…”
Section: Methodsmentioning
confidence: 99%
“…Kadlečík et al (2004) proposed a change in the breeding goal, expanding the single recording of milk production to include recordings of multiple desirable traits which together serve as a basis for the total merit index proposed by Kasarda et al (2008a). This index includes estimated breeding values (EBV) for milk production in kg (BS SR, 2009), for live weight at 210 days of age (Kasarda et al, 2009), and for functional length of production life (Mészáros et al, 2008). The economic importance of these traits was based on studies by Krupová et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Heritability estimates on a log linear scale range from 0.05 to 0.10 (Caraviello et al, 2004b), while on average they range from 0.15 to as high as 0.20 when determined on the original scale (Caraviello et al, 2004a). Using the Weibull PH models, Mészáros et al (2008) reported heritability estimates of 0.05 on a logarithmic scale in Croatian Pinzgau cattle. This concurred with the logarithmic estimates of 0.04 reported earlier by Van der Linde et al (2006) and Chirinos et al (2007).…”
Section: Proportional Hazards Modelsmentioning
confidence: 98%
“…Durr et al, 1999;Caraviello et al, 2004a;Mészáros et al, 2008;M'hamdi et al, 2010;Jovanovic & Raguz, 2011). More than 50% of all member countries of Interbull that evaluate longevity use PH models with sire or sire-maternal grandsire models, although countries such as New Zealand, Ireland, Australia, Great Britain and USA still use the multi-trait animal or sire models (Potocnik et al, 2009;Interbull, 2014).…”
Section: Proportional Hazard Modelsmentioning
confidence: 99%